Case report: Deep sequencing and long-read genome sequencing refine prior genetic analyses in families with apparent gonadal mosaicism in PIK3CD-related activated PI3K delta syndrome - Orellana, Halyn; Yan, Jia; Paul, Alex; Tokita, Mari; Ding, Yan; Ghosh, Rajarshi; Lewis, Katie L.; Davis, Joie; Jamal, Leila; Jodarski, Colleen; Similuk, Morgan; Saucier, Nermina; et al. (Frontiers in Immunology, 2024)
Gonadal and gonosomal mosaicism describe phenomena in which a seemingly healthy individual carries a genetic variant in a subset of their gonadal tissue or gonadal and somatic tissue(s), respectively, with risk of transmitting the variant to their offspring. In families with one or more affected offspring, occurrence of the same apparently de novo variants can be an indicator of mosaicism in either parent. Panel-based deep sequencing has the capacity to detect low-level mosaic variants with coverage exceeding the typical limit of detection provided by current, readily available sequencing techniques. In this study, we report three families with more than one affected offspring with either confirmed or apparent parental gonosomal or gonadal mosaicism for PIK3CD pathogenic variants. Data from targeted deep sequencing was suggestive of low-level maternal gonosomal mosaicism in Family 1. Through this approach we did not detect pathogenic variants in PIK3CD from parental samples in Family 2 and Family 3. We conclude that mosaicism was likely confined to the maternal gonads in Family 2. Subsequent long-read genome sequencing in Family 3 showed that the paternal chromosome harbored the pathogenic variant in PIK3CD in both affected children, consistent with paternal gonadal mosaicism. Detection of parental mosaic variants enables accurate risk assessment, informs reproductive decision-making, and provides helpful context to inform clinical management in families with PIK3CD pathogenic variants.